The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1620/tjem.177.93
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Right Ventricular Free Wall in Dogs with and without Pulmonary Constriction.

Abstract: M., KANAZAWA, M., HANEDA, T. and TAKISHIMA, T. Significance of the Right Ventricular Free Wall in Dogs with and without Pulmonary Constriction. Tohoku J. Exp. Med., 1995, 177 (2), [93][94][95][96][97][98][99][100][101][102][103][104][105][106] To evaluate the role of the right ventricular (RV) free wall in cardiac function, RV and left ventricular (LV) wall segment lengths were measured by ultrasonic crystals in 10 open chest dogs with the pericardium preserved. Right coronary artery (RCA) was perfused separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Nevertheless, we did not show a strong association between TAM and RVEF; marked differences in ranges may also explain the poor relationship between these two variables. Our findings suggest that the degree of RV longitudinal shortening does not appear to contribute significantly to RV ejection; this is also supported by animal models and human studies of RV function 13,14 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, we did not show a strong association between TAM and RVEF; marked differences in ranges may also explain the poor relationship between these two variables. Our findings suggest that the degree of RV longitudinal shortening does not appear to contribute significantly to RV ejection; this is also supported by animal models and human studies of RV function 13,14 …”
Section: Discussionsupporting
confidence: 76%
“…That TFC correlated poorly with RVEF was surprising in light of evidence supporting a dominant role for transverse systolic shortening 14 . Nevertheless, the relationship between transverse shortening and RVEF may only be linear in patients with normal or slightly impaired RV function 13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, an experimental study indicated that contraction of the right ventricular free wall contributed to maintenance of right ventricular ejection function. 18 Active contraction of the free wall may result in a bellows action, which of course may also be influenced by the movement of the ventricular septum and indirectly by that of the left ventricular free wall. In addition, it seems that these myocardial movements depend on bi-ventricular pressures and volumes.…”
Section: F-mp Distance From the Right Ventricular Free Wall To The Mmentioning
confidence: 99%